Attitudes of Public Hospital Nurses in Greece Toward Cultural Diversity and Their Association with Empathy - Gazi, Georgia; Alexias, George; Triantafillidou , Sofia; Togas, Constantinos (British Journal of Healthcare and Medical Research, 2024)
This study aimed to investigate the attitudes of public hospital nurses in Greece toward cultural diversity and explore the relationship between these attitudes and empathy. A 4-month cross-sectional quantitative study was conducted from October 2022 to January 2023. The questionnaires were distributed using the Google Forms platform, and the sample comprised 179 nurses (n=179) employed in public hospitals. The questionnaire encompassed demographic and work-related inquiries, along with sections on cross-cultural health education and the Clinical Culture Competency Questionnaire (CCCQ) and Toronto Empathy Questionnaire (TEQ). Data analysis was carried out using SPSS software, version 28. The results indicated that nurses exhibit a moderate to fairly high level of positive attitudes toward ethnic minority patients, alongside a low level of empathy. Additionally, a positive weak correlation was observed between cultural skills and empathy (r=.223, p<.001), as well as between management of cultural situations and empathy (r=.162, p<.005). Significant differences in nurses’ attitudes toward cultural diversity and empathy were identified based on specific demographic characteristics and their training experiences in intercultural health. In conclusion, this study underscores the importance of nurturing more positive attitudes among nurses toward patients from ethnic minorities. This necessitates a concerted effort to enhance both empathy and training in intercultural health. By fostering these qualities, healthcare professionals can better address the diverse needs of patients, thereby promoting more inclusive and effective healthcare delivery.